2022
DOI: 10.1039/d2ta05530a
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular polyelectrolyte hydrogel based on conjoined double-networks for multifunctional applications

Abstract: A supramolecular polyelectrolyte PVA-PAANa-PAH hydrogel with excellent mechanical properties and superior conductive stability has been fabricated for multifunctional applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…4c). [31][32][33][34][35][36][37][38][39][40][41][42][43] Meanwhile, as displayed in Fig. S4 (ESI †), the PHA organohydrogel sensor also possesses satisfactory response and recovery times of 592 and 595 ms, respectively.…”
Section: Resultsmentioning
confidence: 95%
“…4c). [31][32][33][34][35][36][37][38][39][40][41][42][43] Meanwhile, as displayed in Fig. S4 (ESI †), the PHA organohydrogel sensor also possesses satisfactory response and recovery times of 592 and 595 ms, respectively.…”
Section: Resultsmentioning
confidence: 95%
“…The multiple hydrogen bonds can reversibly break for effectively dissipating energy and the dual-network structures maintain the basic shape of hydrogel during large mechanical deformation. 33 Given its excellent mechanical properties, the GG/PAAm/PA/LiCl hydrogel may be an ideal material for assembling durable flexible wearable strain sensors.…”
Section: Resultsmentioning
confidence: 99%
“…We further compared the advantages of our hydrogel with other research work in terms of GF and electrical conductivity, and the results showed the superior performance of PGC hydrogels (Fig. 3f) [26,43,47,49,61,[63][64][65][66][67][68][69][70][71]. In addition, we tested the response/recovery time (100/150 ms) of the hydrogel sensor during stretching and compared it with other reported work (Fig.…”
Section: Conductivity Of Supramolecular Hydrogel Electronic Skinmentioning
confidence: 88%